The Significance of Switzerland's Enormous Current-Account Surplus - Jarrett, Peter (OECD Economics Department Working Papers, 2008)
Switzerland has had a long-standing surplus on its current account. But over the past 15 years that surplus has surged to levels unmatched by nearly any other OECD country at any point. This paper looks at the surplus from a balance of payments vantage point as well as from the optic of the excess of national saving over domestic investment. It then seeks possible explanations for the uptrend and assesses whether it results to any extent from market, institutional or policy failures that could call for reforms. A number of important measurement issues are raised. But the key recommendation is that the authorities should prepare for a possible sharp increase in the value of the Swiss franc if and when investors engaged in the "carry trade" unwind their positions. To that end they should examine labour, capital and product markets with a view to ensuring they are as flexible as possible and that factors are as mobile as possible, both geographically and sectorally. This will allow any necessary adjustment to a higher exchange rate to be smoothly accommodated. This Working Paper is largely extracted from the 2007 OECD Economic Survey of Switzerland (www.oecd.org/eco/survey/switzerland)